Vocational guidance work for primary education students: the problem and their solutions - Axmedova Malika Dilshod qizi (Genius Journals, 2022)
The orientation of the growing younger generation in the profession, the emergence of their talents in a respected state, the upbringing of a child on the basis of integration.
Keywords: Reader; conversation; mutual respect; listening